(untitled) (Bangladesh Journal of Plant Taxonomy, 2008)
A total of nine taxa of Bulbocheate Agardh are reported from the north-west Barind tract of Bangladesh as new records for the country. These are Bulbochaete crassa Pringsh., B. debaryana Wittr. & Lund. in Wittr., B. elatior Pringsh. var. elatior, B. iyengarii Sarma & Mukh., B. keralense Venk. & Natr., B. minuta West & West, B. nana Wittr. var. chungkingensis Jao, B. pygmaea Pringsh. var. erecta Jao, and B. suberecta (Coll.) Tiff. Keywords: Oedogoniales, Bulbochaete, New records, Bangladesh DOI: 10.3329/bjpt.v15i2.1738 Bangladesh J. Plant Taxon. 15(2): 81-87, 2008 (December) Â